Spatiotemporal changes of cultivated land utilization in black soil region, China based on geo-information Tupu - Dan Li; Guizhen Chen; Zhilong Xi; Pengkai He; Xiuwen Xin; Jiayuan Chen; Hongyu Yu; Guangqing Kang (Scientific Reports)
Abstract In recent years, quantity and quality of cultivated land in black soil region in Northeast China have changed with the continuous strengthening of the breadth and depth of land development, directly affecting food security in China. In this study, land-use data based on geo-information Tupu in 1990, 2000, 2010 and 2020 were selected and the spatiotemporal evolution of cultivated land in Northeast China was analyzed. Meanwhile, driving factors affecting the changes of cultivated land over the past 30 years was also explored. The results indicate that the net increase of cultivated land in the study area is 127.72 km2 (accounting for 0.038% of the study area) from 1990 to 2020, and a trend of “increase-decrease-increase” over the past 30 years can be obtained. The change of cultivated land mainly due to the mutual conversion between cultivated land and forest (net increase: 6024.76 km2), grassland (net increase: 734.08 km2) and construction land (net decrease: 7393. 42 km2). The conversions of cultivated land and forest, grassland and construction land are mainly located in the northeastern, mid-western and southern, and eastern of the study area, and the center of cultivated land within the study area shifted towards the southeast from 1990 to 2010, while the center showed a convoluted trend (moving towards the northwest) during the 2010–2020 period, but the migration speed gradually slowed down. The spatiotemporal pattern changes of cultivated land in the study area from 1990 to 2020 are the comprehensive effects of natural environmental and socio-economic factors, among which slope, elevation, and annual precipitation are the main contributing factors. The conclusion of this study will provide scientific reference for the study of cultivated land utilization and protection in the black soil region in Northeast China.